2019
DOI: 10.1016/j.socscimed.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Community mobilization for rural suicide prevention: Process, learning and behavioral outcomes from Promoting Community Conversations About Research to End Suicide (PC CARES) in Northwest Alaska

Abstract: Rationale This study evaluates the process and preliminary outcomes of Promoting Community Conversations About Research to End Suicide (PC CARES), an intervention that brings key stakeholders together so they can discuss suicide prevention research and find ways to put it into practice. Originally piloted in remote and rural Alaskan communities, the approach shows promise. Method Using a multi-method design, the study describes a series of locally-facilitated “learning circles” over 15 months and their preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…There seemed to be a strong desire to share northern-based knowledge on the subject rather than adapting southern programmes. As mentioned by our partners, suicide prevention programmes were being developed across Inuit Nunangat and in other northern regions, including Alaska [30,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seemed to be a strong desire to share northern-based knowledge on the subject rather than adapting southern programmes. As mentioned by our partners, suicide prevention programmes were being developed across Inuit Nunangat and in other northern regions, including Alaska [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…CoPs must offer a safe environment to help foster a feeling of belonging and equality within the community. CoPs are recognized as a promising approach in health, education and social services and, more specifically, in mental health promotion and suicide prevention [30,35].…”
Section: Developing a Community Of Practice (Cop)mentioning
confidence: 99%
“…Research done in partnership with AIAN communities has moved towards innovation of alternative methods that are equally rigorous, yet ethically and culturally responsive. For example, to address small sample size and community desire to reduce burden on participants Wexler et al (2019) take an innovative multimethod approach to evaluate preliminary outcomes of the Promoting Community Conversations About Research to End Suicide using focus group data, individual data, and social network analysis. Another example of innovation to RCT design in AIAN communities can be found in the Thiwáhe Gluwáš'akapi (Sacred Home in Which Family is Made Strong) project.…”
Section: Research Design and Approachesmentioning
confidence: 99%
“…PC-CARES has demonstrated feasibility and fidelity when implemented by local facilitators in remote, rural Alaska Native communities. Participants strengthened their 'community of practice' and showed positive changes in perceived knowledge, skills, and attitudes, and prevention behaviors from baseline to follow-up (Wexler, et. al, 2019).…”
Section: Recent Intervention Development Based In a Protective Factor Frameworkmentioning
confidence: 99%
“…Recent research with American Indian and Alaska Native (AIAN) youth, a group identified at vastly heightened suicide risk (DHHS, 2012b), offers promising fresh insights and potential solutions. AIAN suicide research provides numerous innovations in prevention science including examples of successful intervention implementation and outcomes (Allen et al, 2018;Cwik et al, 2014;Wexler et al, 2019). Notably, much of this work expands the aims of suicide prevention beyond tertiary prevention at the individual level (Wexler et al, 2015) and emphasizes the distinctive contribution of culture in effective intervention (Manson, 2020).…”
mentioning
confidence: 99%